Nghiên cứu mối tương quan giữa nồng dộ HBsAg với HBV-DNA ở bệnh nhân nhiễm virut viêm gan B mạn - Hương, Nguyễn Thị Thu; Hương, Phan Thị Minh; Hiền, Hoàng Thị Thanh; Vũ, Trương Đình; Chi, Nguyễn Thị Kim (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.